Strategies for New Zealand manufacturing small and medium sized enterprises going global : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University, Turitea, Palmerston North, New Zealand - Watts, Tony (Massey University, 2008)
The strategies to employ when a small to medium sized enterprise (SME) enters the international market are important issues for a business to consider. This research study addresses the question “What strategies will position New Zealand manufacturing small and medium sized enterprises for international markets?” It is intended to compare various strategies for going global, discovering these through a literature review and personal interviews with New Zealand businesses who have successfully globalised. The research studies globalisation within manufacturing small and medium sized enterprises (SMEs) in New Zealand. It explores strategies available in order to discover their advantages and disadvantages, and suggests key strategic directions for New Zealand manufacturing SME’s to use when entering into international markets. The research is intended to benefit New Zealand SME’s considering entering the international market place, which in turn will contribute towards benefiting New Zealand as a whole as it endeavours to position itself in the international competitive arena. Specific strategies for New Zealand manufacturing SME’s wishing to establish global markets are explored with implications for theory, research, and business practices. A case study approach was adopted, with multiple research methods used to gather information for the study. An experience survey in the form of personal interviews was used to gather a range of views from people with knowledge and experience in exporting to international markets. Documents were analysed, together with information gained through the interviews to compile case histories of the businesses that participated in this research. Strategies relevant to going global were identified in a literature review and these strategies were compared with actions and directions taken by the businesses interviewed. The analysis of the findings reveals congruence with theoretical strategies for globalisation of SMEs identified in previous studies; however it was found that decisions made when going global were highly dependent on the individual circumstances that a business finds itself in, rather than committing to strategies based on assumptions from academic studies. The businesses involved in this study went global through opportunities more so than strategic purpose. They had not set out to be a global enterprise, however when the opportunities arose their globalisation effort needed total commitment. Their experiences are discussed in this study and have relevance for other firms looking to go global.
Keywords: International markets; Small business; Globalisation strategies; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management